Hubungan ASI eksklusif terhadap terjadinya diare akut di Puskesmas III Denpasar Utara periode 2018 - I Putu Gede Danika Adikarya; Ni Nyoman Metriani Nesa; Made Sukmawati (DiscoverSys Inc., 2019)
Introduction: Diarrhea is still a public health problem in developing countries, including Indonesia, because of its high morbidity and mortality. Breast milk is one of the important factors to reduce mortality and morbidity due to diarrhea. The aim of this study was to determine the relationship of exclusive breastfeeding to the occurrence of acute diarrhea. This research is analytic research with cross sectional method.Method: The study was carried out in Community Health Centre III Subdistrict of North Denpasar from October to November 2018. The research subjects were taken by consecutive sampling. Data analysis used the prevalence ratio calculation and chi square test to determine the relationship between exclusive breastfeeding and the incidence of diarrhea.Result: In this study the results of acute diarrhea patients in the exclusive breastfeeding group were 17 children and non-exclusive breastfeeding as many as 31 children. Subjects who did not experience acute diarrhea in the excluded breastfeeding group were 28 children and in the non-exclusive breastfeeding group as many as 14 children. The results of statistical analysis showed the value of p=0.003 (p<0.05)Â PR=0.514 CI 95% (0.115-0.656).Conclusion: Exclusive breastfeeding has a significant relationship with the incidence of acute diarrhea and is a protective factor for the incidence of diarrhea.